Evaluate Student Learning Outcomes Through the Quizizz Platform - Firyal Nabilah Afifah; Putri Rahmawati; Asya Izzati Virliana; Bunga Dwi Wulan (FKIP Universitas Halu Oleo, 2023)
Education is the most important pillar of national development, and innovation of learning methods is the key to improving the quality of education. Currently, the development of information technology has a great impact on the world of education. As the use of technology in learning increases, there is a growing need to assess the effectiveness of technology on student learning outcomes. Quizizz is one of the popular platforms that incorporates gaming elements in learning, offering various features such as interactive online quizzes This research aims to analyze the effectiveness of the Quizizz platform as a tool for evaluating students' learning outcomes. The method used by the author in this study is a literature study method where the author collects various library data sourced from journals that have been indexed by Sinta. Based on the results of the analysis, the use of the Quizizz platform is very helpful and makes it easier for educators to carry out online-based evaluations. With easy access anywhere and anytime, flexibility and efficiency that is unlimited by space and time. And with all the complex features that have been presented by Quizizz, in fact, it has been able to improve the results of student evaluations, while still upholding integrity and honesty as intellectuals. From the literature analysis, it was found that the utilization of Quizizz as a learning evaluation tool offers advantages in interactivity, flexibility, and user-friendliness. Features such as avatars, music, and rankings enhance student engagement. Although challenges such as technological readiness and security concerns exist, efforts such as technology training can help address them.